2008
DOI: 10.1128/aac.00158-08
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Plasmid-Mediated Quinolone Resistance in Klebsiella pneumoniae Isolates Possessing bla KPC in the United States

Abstract: The presence of plasmid-mediated quinolone resistance genes [i.e., qnrA, qnrB, qnrS, aac(6)-Ib-cr, and qepA] was evaluated among 42 bla KPC -containing Klebsiella pneumoniae isolates collected in the eastern United States. One isolate carried the bla KPC-3 and qnrB19 genes on the same conjugative plasmid, whereas another carried the bla KPC-3 and qnrA1 genes on separate plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 15 publications
1
52
0
3
Order By: Relevance
“…Using specific primers and sequencing (12), a qnrB19 gene was detected in the parental strain. These results were similar to those of previous reports which demonstrated that KPC-producing isolates are resistant not only to all ␤-lactam antibiotics, including carbapenems, but also to some non-␤-lactam antibiotics, such as fluoroquinolones (13,14).…”
supporting
confidence: 82%
“…Using specific primers and sequencing (12), a qnrB19 gene was detected in the parental strain. These results were similar to those of previous reports which demonstrated that KPC-producing isolates are resistant not only to all ␤-lactam antibiotics, including carbapenems, but also to some non-␤-lactam antibiotics, such as fluoroquinolones (13,14).…”
supporting
confidence: 82%
“…P, K. pneumoniae K1 isolated from the 2nd Affiliated Hospital of Zhejiang University (producing KPC-2, TEM-1, SHV-11 and CTX-M-14); t, E. coli transconjugant; M, strain producing TEM-28 (pI 6.1), SHV-7 (pI 7.6) and ACT-1 (pI 9.0). Monteiro et al, 2009;Naas et al, 2008;Tsakris et al, 2008;Yigit et al, 2003) and some encoded qnr (Chmelnitsky et al, 2008;Endimiani et al, 2008;Mendes et al, 2008). Unlike these, most bla KPC -encoding plasmids in this study were associated with four drug-resistance genes.…”
Section: Pcr and Dna Sequence Analysismentioning
confidence: 99%
“…Soon afterward, KPC-3 was founded in Klebsiella pneumoniae [39] and in other Enterobacteriaceae isolated in USA [11,[40][41][42]. KPC-3 has never been reported outside the USA, until 2007.…”
Section: The Kpc -Enzymes: Characteristics and Epidemiologymentioning
confidence: 99%
“…The bla KPC genes have usually been identified in large plasmids. These plasmids also carry aminoglycosideresistance determinants, and have been associated with other antibiotic-resistance genes such as the most widespread ESBL genes or quinolones-resistance determinants (QnrA, QnrB) [25,31,40,[55][56][57].…”
Section: Molecular Characterization Of Bla Kpc Genes Encoded Kpc Carbmentioning
confidence: 99%